Alleviation of Meloidogyne incognita induced biotic stress in Daucus carota by nitrogen: Insights into cellular viability and reactive oxygen species of the host - Shakeel, Adnan; Khan, Abrar Ahmad; Sayed, Samy; Karabulut, Fadime (Academic Press Ltd- Elsevier Science Ltd, 2023)
Developing innovative nematode management solutions is becoming more important since ecologically haz-ardous nematicides are being phased out of the global markets. As a result, alternative measures that are less harmful to the environment are preferred for dealing with the root-knot nematodes which cause huge economic losses to farmers. This investigation was therefore, entailed to find the optimum nitrogen fertilizer rate to maximize plant growth promotion and upsurge nematicidal activity, while minimizing the harmful effects on environment. Among the various nitrogen fertilizer treatments from 50 kg/ha to 200 kg/ha, the most effective concentration was found to be 150 kg/ha N (U150Mi) at which significant (P <= 0.05) improvements in growth, yield, photosynthetic pigments, nitrate reductase activity (NRA), protein, and carbohydrate content of carrot were observed as compared to the nematode inoculated untreated plants. Scanning electron microscopy showed that compared to the untreated inoculated control, the stomatal characteristics of carrot improved significantly at U150Mi (150 kg/ha N). Laser confocal microscopy illustrated that nitrogen fertilizer markedly improved the cellular viability of carrot at U150Mi (150 kg/ha N) in comparison to nematode infected plants. Histochemical analysis revealed that the reactive oxygen species (ROS) marker, superoxide anion radicals were significantly scavenged by the enhanced antioxidant defense system of carrot at U150Mi (150 kg/ha N). In vitro studies demonstrate that nitrogen fertilizer has nematicidal properties that were dose dependent. Gall/egg mass indices and reproduction factor were dramatically reduced when U150Mi (150 kg/ha N) was applied to carrot plants inoculated with Meloidogyne incognita.
Keywords: Disease management; Nitrogen; Nematicide; Root-knot nematode; Root-vegetables